2020
DOI: 10.3389/fmicb.2020.01548
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Mucosa-Associated Microbial Signatures of Early Gastric Cancer

Abstract: Alterations in the microbiome are associated with the development of gastric cancer. Our study aimed to identify dysbiotic features in early gastric cancer (EC). The gastric microbiome was assessed in EC (n = 30), advanced gastric cancer (AC) (n = 30), and chronic gastritis (CG) (n = 60). The results demonstrated significant differences in the microbial profile and composition between EC and AC, suggesting alterations associated with gastric cancer progression. Linear discriminant analysis (LDA) effect size (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 54 publications
3
29
0
Order By: Relevance
“…However, another study showed that the bacterial diversity reduced gradually from normal, intestinal metaplasia, GC, gastritis to atrophy ( Gantuya et al, 2020 ). Moreover, microbial diversity was found to be increased in advanced-stage GC compared to the early stage, which did not differ significantly from that in chronic gastritis ( Wang L. et al, 2020 ). Novosphingobium , Ralstonia , Ochrobactrum , Anoxybacillus , and Pseudoxanthomonas were enriched in early GC whereas Burkholderia , Tsukamurella , Uruburuella , and Salinivibrio were more abundant in advanced as compared to early GC ( Wang L. et al, 2020 ).…”
Section: Helicobacter Pylori Infection and Gastric Microbiommentioning
confidence: 70%
See 3 more Smart Citations
“…However, another study showed that the bacterial diversity reduced gradually from normal, intestinal metaplasia, GC, gastritis to atrophy ( Gantuya et al, 2020 ). Moreover, microbial diversity was found to be increased in advanced-stage GC compared to the early stage, which did not differ significantly from that in chronic gastritis ( Wang L. et al, 2020 ). Novosphingobium , Ralstonia , Ochrobactrum , Anoxybacillus , and Pseudoxanthomonas were enriched in early GC whereas Burkholderia , Tsukamurella , Uruburuella , and Salinivibrio were more abundant in advanced as compared to early GC ( Wang L. et al, 2020 ).…”
Section: Helicobacter Pylori Infection and Gastric Microbiommentioning
confidence: 70%
“…• Signet-ring cell carcinomas were significantly enriched in the phyla Fusobacteria, Bacteroidetes, Patescibacteria, whereas in the adenocarcinoma type, Proteobacteria and Acidobacteria phyla were found advanced-stage GC compared to the early stage, which did not differ significantly from that in chronic gastritis (Wang L. et al, 2020). Novosphingobium, Ralstonia, Ochrobactrum, Anoxybacillus, and Pseudoxanthomonas were enriched in early GC whereas Burkholderia, Tsukamurella, Uruburuella, and Salinivibrio were more abundant in advanced as compared to early GC (Wang L. et al, 2020). However, another study reported that there was no significant difference in microbial community composition between early-and late-stage GC, while microbial richness decreased from normal to peritumoral to tumoral tissues (Liu et al, 2019a).…”
Section: Authors Year Sample Size Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Recent molecular analysis reveals bacteria of the gastric microbiome are mainly from the phyla Proteobacteria, Firmicutes, Bacteroidetes, Actinobacteria, and Fusobacteria[ 9 ]. In GC, the microbiome was altered substantially[ 10 , 11 ]. Data of studies on gnotobiotic mice demonstrate that the presence of artificial microbiota in the stomach promotes the development of H. pylori induced cancer[ 12 ].…”
Section: Introductionmentioning
confidence: 99%